1998
DOI: 10.1002/(sici)1097-4628(19980808)69:6<1203::aid-app17>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of solid-state polymerization with microwave energy

Abstract: This work reports on using microwave energy to increase the rate of solidstate polymerization for PET and nylon 66. Theoretical analysis and experimental evidence show that the increase in polymerization rate is not due to an increase in the bulk temperature. Instead, the effect is consistent with directed heating of the condensate leading to enhanced diffusion rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 5 publications
0
24
0
2
Order By: Relevance
“…Section 2.2). [24] The high-pressure synthesis of polyamides was investigated by Pourjavadi et al for the Yamazaki phosphorylation reaction of aliphatic dicarboxylic acids (x ¼ 2, 4, 6, 8) and aromatic diamines (like 1,4-phenylendiamine and 2,5-bis-(4-aminophenyl)-3,4-diphenylthiophene). [25] The educts were dissolved in N-methylpyrrolidone (NMP) and transferred to the (domestic) microwave oven in a polyethylene screw-capped cylinder.…”
Section: Polyamidesmentioning
confidence: 99%
“…Section 2.2). [24] The high-pressure synthesis of polyamides was investigated by Pourjavadi et al for the Yamazaki phosphorylation reaction of aliphatic dicarboxylic acids (x ¼ 2, 4, 6, 8) and aromatic diamines (like 1,4-phenylendiamine and 2,5-bis-(4-aminophenyl)-3,4-diphenylthiophene). [25] The educts were dissolved in N-methylpyrrolidone (NMP) and transferred to the (domestic) microwave oven in a polyethylene screw-capped cylinder.…”
Section: Polyamidesmentioning
confidence: 99%
“…(vii) Yields were almost quantitative for the runs performed according to synthesis mode (1) and about 80% in the case of synthesis mode (2), probably due to a loss of monomer by evaporation. …”
Section: Microwave Polymerisationmentioning
confidence: 96%
“…Diffusion limited polymerizations of polyethylene terephthalate (PET) and nylon-6,6 were studied by Mallon et al [39]. It was concluded that microwaves could selectively excite the condensate in the polymer to cause higher diffusion rates and subsequently promote fusion of the end groups in solid-state polymerization (SSP) of PET and nylon-6,6.…”
Section: The Role Of Polar Molecules High Boiling Solvents and Hetermentioning
confidence: 99%